Health Effects of Low Level Radiation: When will We Acknowledge the Reality? - J. M. Cuttler (SAGE Publishing, 2007)
The 1986 April 26 th Chernobyl event was the worst nuclear power accident-it killed 31 people. Its significance was exaggerated immensely because of the pervasive fear of ionizing radiation that has been indoctrinated in all of humanity. In reality, our environment includes radiation from natural sources, varying widely in intensity, to which all living things have adapted. The effect of radiation on organisms is primarily on their damage control biosystem, which prevents, repairs and removes cell damage. Low doses stimulate this system, while high doses inhibit it. So low doses decrease the incidences of cancer and congenital malformations; high doses have the opposite effect. Efforts by radiation protection organizations to lower exposures to (human-made) radiation to as low as reasonably achievable (ALARA) provide no benefit. They only create inappropriate fear-barriers to very important applications of nuclear technology in energy production and medicine.